EFFECT OF CUSTOMER EXPERIENCE AND FEAR OF MISSING OUT (FOMO) ON REPURCHASE INTENTION THROUGH CUSTOMER TRUST AS AN INTERVENTION VARIABLE : SKINTIFIC CUSHIONE SURVEY ON SHOPEE - Rika Aulia (MANAJEMEN DEWANTARA, 2025)
The rapid growth of e-commerce in Indonesia has reshaped consumer behavior in the beauty industry, with Shopee leading the market and Skintific cushion gaining strong popularity. Despite this, maintaining repurchase intention remains a challenge. This study investigates the effect of customer experience and fear of missing out (FOMO) on repurchase intention, with customer trust as a mediating variable. Using a quantitative method, 105 Shopee users who had purchased Skintific cushion were surveyed through questionnaires, and the data were analyzed with PLS-SEM (smartpls 4.0). The results indicate that customer experience positively and significantly affects customer trust, and customer trust in turn significantly drives repurchase intention. However, FOMO does not significantly influence customer trust or repurchase intention. Mediation analysis further shows that customer experience impacts repurchase intention through customer trust, while FOMO does not. This study emphasizes that improving customer experience and strengthening trust are more effective strategies than relying on FOMO- driven marketing